Fertilizer Factory Port Conveyor Optimization Design System With Outseal PLC and HMI - Rovi Maulidani Syela; Denny Irawan (G-Tech: Jurnal Teknologi Terapan, 2025)
The development of automation systems in industry is increasingly rapid, especially in the field of material control and distribution. Automation systems are designed to simplify human work and stabilize the performance of industrial machines to be more efficient and reliable. This article discusses the design and implementation of a prototype of an automatic conveyor system in the port area that functions to support the material distribution process to the fertilizer factory. This system uses the Outseal Nano Programmable Logic Controller (PLC) as the main controller and the Haiwell Human Machine Interface (HMI) as a remote monitoring and control system. The main objective of the design is to reduce buildup and prevent material spillage during the transportation process from the port to the production area. Test results show that the automatic conveyor system is able to operate stably at an operational temperature of 45°C and a Moisture Quantity (MQ) value of at least 30%, without significant disruption to the transportation process. The implementation of this system resulted in an increase in material distribution efficiency of 27.8% compared to the manual system, and reduced material handling time by up to 22%. In addition, the error rate in material distribution was reduced by up to 15%, which contributed to increased accuracy and work safety in the port area. Overall, this automation system has been proven to increase the efficiency and reliability of the material distribution process, as well as being an effective solution to overcome logistical and operational problems in the port industry environment.